School structure, bullying by teachers, moral disengagement, and students’ aggression: A mediation model - Ivaniushina, Valeria; Alexandrov, Daniel (Frontiers in Psychology, 2022)
Aim: Understanding interrelations between the factors predicting students’ aggressive behavior is a priority for bullying-prevention programs. Previous studies have demonstrated that an authoritative school climate, characterized by a clear and fair disciplinary structure, is associated with a decrease in bullying. Our study contributes to the existing literature by exploring two possible mechanisms linking school disciplinary structure and students’ aggression. In particular, we tested student moral disengagement and bullying by teachers as mediational pathways from school climate to students’ aggressive behavior. Method: We used a regionally representative sample of 213 schools that participated in a school climate survey in Kaluga Oblast (a federal subject of Russia) in 2019. The analytic sample contained the anonymous responses of 16,809 students from grades 6–9 (12–15 years old); 51% of the respondents were girls. The analytical procedure consisted of structural equation modeling (SEM), which was implemented in Mplus 8.7. Results: The mediation model fit the data well, suggesting that the clarity and fairness of school rules negatively predicted peer aggression, while student moral disengagement and bullying by teachers independently and partially mediated this association. Conclusion: Prevention programs designed to increase the fairness and consistency of rules in school, eliminate bullying and humiliation from teachers, and decrease students’ moral disengagement may reduce violence and victimization at school.